A Simplified Mathematical Model for Heating-Induced Thermal Runaway of Lithium-Ion Batteries. Issue 1 (6th January 2021) - Chen, Haodong; Buston, Jonathan E. H.; Gill, Jason; Howard, Daniel; Williams, Rhiannon C. E.; Read, Elliott; Abaza, Ahmed; Cooper, Brian; Wen, Jennifer X.
Abstract : The present study aims to develop a simplified mathematical model for the evolution of heating-induced thermal runaway (TR) of lithium-ion batteries (LIBs). This model only requires a minimum number of input parameters, and some of these unknown parameters can be obtained from accelerating rate calorimeter (ARC) tests and previous studies, removing the need for detailed measurements of heat flow of cell components by differential scanning calorimetry. The model was firstly verified by ARC tests for a commercial cylindrical 21700 cell for the prediction of the cell surface temperature evolution with time. It was further validated by uniform heating tests of 21700 cells conducted with flexible and nichrome-wire heaters, respectively. The validated model was finally used to investigate the critical ambient temperature that triggers battery TR. The predicted critical ambient temperature is between 127 °C and 128 °C. The model has been formulated as lumped 0D, axisymmetric 2D and full 3D to suit different heating and geometric arrangements and can be easily extended to predict the TR evolution of other LIBs with different geometric configurations and cathode materials. It can also be easily implemented into other computational fluid dynamics (CFD) code.